Microstructures in arc-welded Al10Co25Cr8Fe15Ni36Ti6 and Al10.87Co21.74Cr21.74Cu2.17Fe21.74Ni21.74 multi-principal element alloys - Shen, Jiajia (2023)
Funding Information: JPO and JS acknowledge Fundação para a Ciência e a Tecnologia (FCT - MCTES) for its financial support via the project UID/00667/2020 (UNIDEMI). JS acknowledges the China Scholarship Council for funding the Ph.D. grant (CSC NO. 201808320394). JPO acknowledges funding by national funds from FCT - Fundação para a Ciência e a Tecnologia, I.P. in the scope of the projects LA/P/0037/2020, UIDP/50025/2020 and UIDB/50025/2020 of the Associate Laboratory Institute of Nanostructures, Nanomodelling and Nanofabrication – i3N. The authors acknowledge DESY (Hamburg, Germany), a member of the Helmholtz Association HGF, for the provision of experimental facilities. Beamtime was allocated for proposal I-20210899 EC. The research leading to this result has been supported by the project CALIPSOplus under the Grant Agreement 730872 from the EU Framework Programme for Research and Innovation HORIZON 2020. CF and ACM gratefully acknowledge partial financial support for this research by the Institute of Materials Research (IMR) at The Ohio State University under a 2017 Exploratory Materials Research Grant, and by the American Welding Society (AWS) under an AWS Graduate Research Fellowship Grant. Electron microscopy was performed at the Center for Electron Microscopy and Analysis (CEMAS) at The Ohio State University. Funding Information: JPO and JS acknowledge Fundação para a Ciência e a Tecnologia (FCT - MCTES) for its financial support via the project UID/00667/2020 (UNIDEMI). JS acknowledges the China Scholarship Council for funding the Ph.D. grant (CSC NO. 201808320394 ). JPO acknowledges funding by national funds from FCT - Fundação para a Ciência e a Tecnologia, I.P., in the scope of the projects LA/P/0037/2020, UIDP/50025/2020 and UIDB/50025/2020 of the Associate Laboratory Institute of Nanostructures, Nanomodelling and Nanofabrication – i3N. The authors acknowledge DESY (Hamburg, Germany), a member of the Helmholtz Association HGF, for the provision of experimental facilities. Beamtime was allocated for proposal I-20210899 EC. The research leading to this result has been supported by the project CALIPSOplus under the Grant Agreement 730872 from the EU Framework Programme for Research and Innovation HORIZON 2020. CF and ACM gratefully acknowledge partial financial support for this research by the Institute of Materials Research (IMR) at The Ohio State University under a 2017 Exploratory Materials Research Grant, and by the American Welding Society (AWS) under an AWS Graduate Research Fellowship Grant. Electron microscopy was performed at the Center for Electron Microscopy and Analysis (CEMAS) at The Ohio State University. Publisher Copyright: © 2022 The Authors